Croatian readers' societies of Central Istria at the turn of the 19th and the 20th century: Croatian Reading room in Sv. Petar u Šumi (Libellarium: journal for research in the field of information and related sciences, 2021)
Purpose. The aim of the paper is to present the historical development of the reading movement in Istria in the second half of the 19th and the first half of the 20th century, with emphasis on the reading societies of Central Istria on the example of the Croatian reading room in Sv. Petar u Šumi.Approach/methodology. The research of the reading movement was based on the analysis of the content of archival material and publications: the original records and other documents of the Croatian Reading Room in Sv. Petar u Šumi, which are located in the Parish Office, the material of the Historic Archive in Pazin and the texts published in the newspapers Naša sloga and Pučki prijatelj.Findings. The first part of the paper gives an overview of the history of the reading movement in Istria in the second half of the 19th and the first half of the 20th century. The second part reflects on the establishment of reading societies in Central Istria, with a special overview of the Croatian Reading Room in Sv. Petar u Šumi. Although most of the reading rooms of the National Revival period have no preserved original materials, the activities of the Croatian Reading Room in Sv. Petar u Šumi can be reconstructed on the basis of the preserved sources. This paper provides an overview of the establishment of the Reading Room, describes the conditions and types of membership and provides the lists of acquired publications. It also gives the historical and political context of the Reading Room.Originality. The paper contributes to determining the basic features of the development of the reading movement in Central Istria in the second half of the 19th and the first half of the 20th century. New insights are brought on the work of the Croatian Reading Room in Sveti Petar u Šumi. In addition, some factual errors that were repeated in secondary sources have been corrected, too. Keywords: Central Istria, reading movement, reading room, reading societies, Sv. Petar u Šumi
Keywords: reading room; reading movement; Sv. Petar u Šumi; central Istria; reading societies